(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The authors consider the proposed method of determining the primary and secondary sludge of two adjacent alternately depressed and loaded piles, which takes into account the effect of the method of immersion, the distance between them and the level of loading. Keywords:primary and secondary precipitation ofsingle depressed and prismatic piles driven piles.